ABM Proceedings 2018
DOI: 10.5151/2594-357x-31411
|View full text |Cite
|
Sign up to set email alerts
|

Uso Sustentável Da Água Diante Da Recessão Hídrica Na Samarco Mineração S.A.

Abstract: Resumo A mineração, sendo uma importante fonte de recursos primários para vários setores industriais, possui representativa participação na economia brasileira. Apesar dessa importância no contexto econômico, os impactos ambientais oriundos desta atividade são consideráveis, especialmente aqueles relacionados aos recursos hídricos. Algumas mineradoras incorporaram a água como um fator estratégico para a sobrevivência no longo prazo,gerenciando os recursos hídricos através do controle de componentes multidiscip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
0
0
Order By: Relevance
“…The Goldberg cut-off point was used to assess the degree of energy intake bias reported by the pregnant women [53]. For this the following parameters were adopted: Basal Metabolic Rate (BMR) assessed from the Schofield [54] equations using pre-gestational weight and the expected additional energy for each gestational trimester (85, 285, and 475 kcal, respectively) [55]; Physical Activity Level (PAL) equal to 1.4 [56]; within-subject variation in energy intake equal to 23.0%; within-subject variation in repeated BMR measurements equal of 8.5%; total (between-subject) variation in PAL equal to 15.0%; and the number of days of diet assessment equal to 1, since not all pregnant women had two 24-hour recalls [53].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Goldberg cut-off point was used to assess the degree of energy intake bias reported by the pregnant women [53]. For this the following parameters were adopted: Basal Metabolic Rate (BMR) assessed from the Schofield [54] equations using pre-gestational weight and the expected additional energy for each gestational trimester (85, 285, and 475 kcal, respectively) [55]; Physical Activity Level (PAL) equal to 1.4 [56]; within-subject variation in energy intake equal to 23.0%; within-subject variation in repeated BMR measurements equal of 8.5%; total (between-subject) variation in PAL equal to 15.0%; and the number of days of diet assessment equal to 1, since not all pregnant women had two 24-hour recalls [53].…”
Section: Discussionmentioning
confidence: 99%
“…The iodized salt is the primary source of iodine in Brazil 27 , which explains the close relationship between iodine intake and the amount of salt used for food preparation, cooking, and consumption 56 . Exploratory analysis of data (results not presented on tables) showed that pregnant women who reported having the "habit of adding salt to meals after preparing/cooking" also had iodine intake (164.1 mcg; 95% CI: 163.8-164.5) slightly higher than those of pregnant women who reported not having this habit (162.5 mcg; 95% CI: 162.3-162.7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations